2020
DOI: 10.1007/s10661-019-8023-x
|View full text |Cite
|
Sign up to set email alerts
|

A multi-criteria evaluation system for arable land resource assessment

Abstract: This study proposed a multi-criteria evaluation system for arable land resources by combining the soil integrated fertility index (IFI) with a soil cleanliness index (based on heavy metals and metalloid content). A total of 16 typical arable land units in Chongming District, China, were evaluated using the proposed evaluation system based on 104 collected soil samples in 16 towns. The comprehensive soil evaluation scores of arable lands in 16 towns were in the range of 90.7 to 99.2 with a mean of 96.2, indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…quality indexes (SQIs) have focused on wetlands, cultivated land, and farmland [14][15][16][17] , but few have focused on grassland soil quality 18 . SQIs are important for evaluating grassland ecosystems.…”
mentioning
confidence: 99%
“…quality indexes (SQIs) have focused on wetlands, cultivated land, and farmland [14][15][16][17] , but few have focused on grassland soil quality 18 . SQIs are important for evaluating grassland ecosystems.…”
mentioning
confidence: 99%
“…In recent years, a few scholars began to explore the comprehensive assessment methods of soil quality. Li et al [12] established a multi-criteria assessment system for arable land resources by using the soil comprehensive fertility index and Nemerow index. Fan et al [13] calculated the soil environmental index (SEI) and soil fertility index (SFI) by improving the Nemerow index, and, finally, obtained the soil quality index (SQI) by using the multi-criteria quantitative method.…”
Section: Introductionmentioning
confidence: 99%
“…In modern times, scientists and soil specialists carry out numerous works to study the features and determine the direction of natural and anthropogenic processes occurring in natural ecosystems [1][2][3][4][5][6]. Numerous studies have shown that as a result of constantly changing soil-environmental conditions and increased anthropogenic impact, there is an increase in the impact of the physicochemical properties of soils on the environment, since any changes in the soil cover lead to a change in environmental conditions.…”
Section: Introductionmentioning
confidence: 99%